Vitamin B12 Prevents Cimetidine-Induced Androgenic Failure and Damage to Sperm Quality in Rats - Beltrame, Flávia Luciana; de Santi, Fabiane; Vendramini, Vanessa; Cabral, Regina Elizabeth Lourenço; Miraglia, Sandra Maria; Cerri, Paulo Sérgio; Sasso-Cerri, Estela (Frontiers in Endocrinology, 2019)
Cimetidine, used as an anti-ulcer and adjuvant treatment in cancer therapy, causes disorders in the male reproductive tract, including steroidogenesis. However, its effect on sperm quality and male fertility has been poorly addressed. Since vitamin B12 has demonstrated to recover spermatogonia number and sperm concentration in cimetidine-treated rats, we evaluated the impact of cimetidine on sperm quality and fertility potential and whether vitamin B12 is able to prevent the harmful effect of this drug on steroidogenesis and sperm parameters. Adult male rats were treated for 52 consecutive days as follows: cimetidine group (100mg/kg of cimetidine), cimetidine/vitamin B12 group (100mg/kg of cimetidine + 3µg vitamin B12), vitamin B12 group (3µg vitamin B12) and control group (saline). Serum testosterone levels and immunofluorescence associated to Western blot for detection of 17β-HSD6 were performed. Sperm morphology and motility, mitochondrial activity, acrosome integrity, DNA integrity by Comet assay, lipid peroxidation as well as fertility potential were analyzed in all groups. Apoptotic spermatids were also evaluated by caspase-3 immunohistochemistry. In the cimetidine-treated animals, reduced serum testosterone levels, weak 17β-HSD6 levels and impaired spermiogenesis were observed. Low sperm motility and mitochondrial activity was associated with high percentage of sperm tail abnormalities, and the percentage of spermatozoa with damaged acrosome and DNA fragmentation increased. MDA levels were normal in all groups, indicating that the cimetidine-induced changes are associated to androgenic failure. In conclusion, despite the fertility potential of rats was unaffected by the treatment, the sperm quality was significantly impaired. Therefore, considering a possible sperm-mediated transgenerational inheritance, the long term offspring health needs to be investigated. The administration of vitamin B12 to male rats prevents the androgenic failure and counteracts the damage inflicted by cimetidine upon sperm quality, indicating that this vitamin may be used as a therapeutic agent to maintain the androgenic status and the sperm quality in patients exposed to androgen disrupters.